A Novel Subspecies of Didymella acutilobae Causing Leaf Spot in East Asian Hogweed - Gyo-Bin Lee; Weon-Dae Cho; Wan-Gyu Kim (Mycobiology)
During disease surveys in 2021 and 2022, outbreaks of leaf spot were observed in East Asian hogweed (Heracleum moellendorffii) plants in fields located in Pyeongchang and Yeongwol, Gangwon Province, Korea. The disease incidence in the fields ranged from 2% to 50%. Based on the morphological and cultural characteristics, four single-conidium fungal isolates from the leaf spot symptoms were identified as Phoma sp. The phylogenetic analyses based on the combined sequences from the four genes (LSU, ITS, TUB2, and RPB2) indicated that the isolates clustered very closely with Didymella acutilobae. However, the morphological and cultural characteristics of the isolates exhibited somewhat distinct differences from those of D. acutilobae, suggesting that the isolates correspond to a novel subspecies. Pathogenicity tests revealed that the isolates caused leaf spot in East Asian hogweed plants. This is the first report of D. acutilobae subsp. heraclei subsp. nov. causing leaf spot in East Asian hogweed.